Missing patients - Ethical questions of clinical surveillance.Results of an Erlangen research project Verschwundene Patienten - Ethische Fragen klinischer überwachung Ergebnisse eines Erlanger Forschungsprojekts - Rexin, Larissa; Fröhlich-Güzelsoy, Leyla; Emrich, Inken; Frewer, Andreas (Zeitschrift für medizinische Ethik, 2016)
During a period of eight years (2006-2014), 305 cases of inpatients that disappeared from the University Hospital Erlangen have been examined and recorded. The data was entered and categorized by four independent encoders. Various aspects were analyzed comparatively in order to provide diverse approaches in furtherance of the optimization processes in hospitals. The focus was particularly laid on vulnerable groups such as patients with dementia and primary mental diseases. Predominately, psychiatric patients were found to be highly represented in the group of patient's injuries. However, the number of missing patients with dementia is comparatively small. Due to the high number of psychiatric patients disappearing, it is indispensable to discuss the ethical concepts of autonomy and the hospital's duty of care.
CRIS-Team Scopus Importer:2025-03-13
Keywords: autonomy versus duty of care; dementia; lost patients; Medical ethics; methods of surveillance